Implementation Of The Entrepreneurial Spirit, Innovation And Salary On Employee Working Motivation - Hertina, Dede; Nurjanah, Ai Siti; Aripin, Ivan; Hidayat, Mohamad Bayu Herdiawan (Jurnal Manajemen Industri dan Logistik, 2023)
This study aims to determine the effect of entrepreneurial spirit, innovation and salary on Employee Motivation. This type of research is associative research, the respondents used in this study amounted to 30 people. The data collection method used in this study was a quantitative method using interview techniques, collecting questionnaires and studying documentation. The data analysis technique used in this study is descriptive analysis, multiple linear regression analysis, classical assumption test (normality test, heteroscedasticity test, multicollinearity test), hypothesis testing (simultaneous significance test (F test), partial significance test (t-test). , coefficient of determination (R2) The results of the study partially show that the entrepreneurial spirit has a positive and significant effect on Employee Work Motivation. Innovation has a positive and significant effect on Employee Work Motivation. Independence is a personal totality that exists in each individual.